DEVELOPMENT OF ECOLOGICAL CULTURE OF STUDENTS IN THE PROCESS OF INTERCULTURAL COMMUNICATION IN FOREIGN LANGUAGE - L. M. Andryukhina; N. Yu. Fadeeva; Gérard De Negri (Russian State Vocational Pedagogical University, 2017)
Introduction. High level of ecological culture in modern society is the most important condition of self-preservation and sustainable development of a human civilization. The processes of globalization force to consider environmental problems with a support on polycultural practice, to take into account national and regional peculiarities in their integrity. Thus, there is the need of the international cooperation not only at the government level, but also at the levels of expert communities, separate groups of society and citizens of the country. Moreover, ecological culture is constantly highlighted in numerous studies, materials and documents of the international forums, summits and conferences of the UN and UNESCO. The aim of this publication is to present the authors' didactic complex of development tools of ecological culture of students, and to show the potential of teaching foreign languages (on the example of French) for students' ecological culture formation by means of development of cross-cultural communicative competence.  Methodology and research methods. Culturological approach has been chosen as a key approach for creation of integrative model of development of ecological culture. The methods involve: the system-based analysis of the content of ecological education; generalization of the theory and practice of implementation of the international strategies of ecological culture development and the analysis of efficiency of the pedagogical technologies intended for this purpose; modeling of the process of formation of ecological culture of students. The diagnostics of components of students' ecological culture has been performed by means of internal questioning, observation, and comparative analysis of group interactions. Also, pedagogical ascertaining experiments, methods of pedagogical design for forms of the educational environment organization, design of the educational programmes, and methods of graphical representation of the research results have been involved. Results and scientific novelty. New principles for the development of ecological culture are singled out. It is stated that intercultural communication is becoming the main mechanism for ecological culture development. Selection of the most productive innovative pedagogical technologies of ecological competence formation of students is carried out. Based on the obtained students' questioning data, the factors promoting the increase of the individual ecological culture level are defined. It has become clear that pupils attach the greatest importance to the participation in international ecological projects, ecological tourism and acquaintance with traditions of different nationalities; at the same time, the role of foreign languages knowledge, reading foreign non-translated sources on environmental issues, and, in general, the importance of cross-cultural communication are estimated by students at a very low level. The authors conclude that relatively little attention is drawn to the issues of ecological culture in the process of foreign languages learning in higher education institutions; students practically do not get the experience of intercultural interaction. The integrative didactic model of ecological culture formation among students is offered. Consequently, intercultural communication plays an important part in the development of ecological culture formation. The educational programme of the course «Development of Ecological Culture of Students in the course of Intercultural Communication in French» is designed on the basis of the proposed model; the results of its approbation are described. Practical significance. The materials of the article can be useful when updating the content of the discipline «Foreign Language», and improvement of the educational process at higher school aimed at the development of students' ecological culture as well.